The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1002/anie.202205784
|View full text |Cite
|
Sign up to set email alerts
|

A Real‐Time In Situ Demonstration of Direct and Indirect Transformation Pathways in CdTe Magic‐Size Clusters at Room Temperature

Abstract: The transformations of colloidal semiconductor magic-size clusters (MSCs) are expected to occur with only discrete, step-wise redshifts in optical absorption. Here, we challenge this assumption presenting a novel, conceptually different transformation, for which the redshift is continuous. In the room-temperature transformation from CdTe MSC-448 to MSC-488 (designated by the peak wavelengths in nanometer), the redshift of absorption monitored in situ displays distinctly continuous and/or step-wise behavior. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 58 publications
4
44
1
Order By: Relevance
“…This important result is not addressed in the previous work on the chemical transformation of MSCs from CdSe to Cu 2 Se and from InP to Cd 3 P 2 . , When the CE reaction occurs on ZnE MSCs, it is our view that a continuous redshift pattern of optical absorption would be observed during the MSC transformation from ZnE to CdE. The uninterrupted pattern is similar to that reported for the intracluster isomerization from CdTe MSC-448 to MSC-488. , After the addition of Cd­(OA) 2 to a dispersion containing ZnSe MSC-299 at RT, the CE reaction (Step 2) that transfers the ZnSe PC to the CdSe PC takes place immediately. Step 2 facilitates Step 1 via which ZnSe MSC-299 transforms to its counterpart ZnSe PC-299.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…This important result is not addressed in the previous work on the chemical transformation of MSCs from CdSe to Cu 2 Se and from InP to Cd 3 P 2 . , When the CE reaction occurs on ZnE MSCs, it is our view that a continuous redshift pattern of optical absorption would be observed during the MSC transformation from ZnE to CdE. The uninterrupted pattern is similar to that reported for the intracluster isomerization from CdTe MSC-448 to MSC-488. , After the addition of Cd­(OA) 2 to a dispersion containing ZnSe MSC-299 at RT, the CE reaction (Step 2) that transfers the ZnSe PC to the CdSe PC takes place immediately. Step 2 facilitates Step 1 via which ZnSe MSC-299 transforms to its counterpart ZnSe PC-299.…”
Section: Resultsmentioning
confidence: 68%
“…In addition to the present CE reaction, we have demonstrated that the binary ME PC can experience another four chemical reactions. They are isomerization to binary ME MSCs, , ,,, substitution reactions followed by isomerization to binary or ternary MSCs (Figure S1B), , ,, addition reactions followed by isomerization to photoluminescent MSCs (Figure S1B), and fragmentation to QDs. , For the reaction of M and E precursors to ME QDs, the E precursor dominates the self-assembly of the M and E precursors that results in the formation of the ME PC with similar stoichiometry. The present finding of the E-dominated, magic self-assembly principle, together with the recent discovery of these binary and ternary MSCs and the successful synthesis of small-size QDs with enhanced yield, demonstrates that we are able to push further “chemical self-assembly” …”
Section: Discussionmentioning
confidence: 99%
“…Very recently, an in situ, real-time examination by optical absorption spectroscopy reveals a strikingly different pathway for the room-temperature evolution of CdTe MSC-488 from CdTe MSC-448. , An unexpected continuous red-shift pattern is observed, in addition to the stepwise one described above. However, the study begins with prenucleation stage samples of CdTe QDs, also called induction period (IP) samples that contain no QDs but the PC for CdTe MSC-371, together with CdTe monomers and fragments (Mo/Fr).…”
Section: Introductionmentioning
confidence: 96%
“…The discrete pattern of the spectrum change usually displays a characteristic isosbestic point located between the two absorption peaks of MSC-1 and MSC-2, without intermediate absorptions. MSCs have their precursor compounds (PC), , and the isomerization pathway is modeled as going through their PCs. ,,, That is from MSC-1 to PC-1, then to PC-2, and finally to MSC-2. Being relatively optically transparent, the PCs do not absorb at the peak position of their counterpart MSCs or to longer wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial observation of (CdSe) 33 and (CdSe) 34 in 2004, intense research activity has focused on the study of synthetic pathways and related formation mechanisms. This field has expanded dramatically since (CdSe) 13 MSCs were synthesized and isolated in solid form by Buhro and co-workers. , In recent years, several stoichiometric MSCs have been isolated in discrete, single-size purity. , For example, Hyeon and co-workers recently reported the crystal structure of a semiconductor Cd 14 Se 13 cluster . It is worth noting that although five members of stoichiometric cadmium-based II–VI MSCs have already been prepared and isolated, ,, the synthesis of pure (CdS) 13 MSCs remains a challenge.…”
Section: Introductionmentioning
confidence: 99%